2019
DOI: 10.1111/1747-0080.12515
|View full text |Cite
|
Sign up to set email alerts
|

Diet quality in adolescents with premenstrual syndrome: A cross‐sectional study

Abstract: Aim: Premenstrual syndrome (PMS) is a complex of symptoms that can seriously affect the quality of life in women. It has been suggested that the nutritional status of adult women may influence the presence and/or severity of PMS symptoms. However, little is known about this association in adolescents. The present study aimed to examine the relationship between diet quality and the presence/severity of PMS symptoms in adolescents. Methods: A case-control study of 272 female students, aged 13-18 years, was condu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
21
1
2

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
2
21
1
2
Order By: Relevance
“…However, no significant associations were found between anthropometric factors and PMS prevalence and symptoms. This finding is in line with the findings of Sadler and colleagues in a cross-sectional study on 974 women in the UK [43] and with the recent finding of Isgin-Atici and colleagues who found no significant differences in anthropometric measurements between PMS cases and their counterpart controls in Turkey [31]. However, this contradicts reports in Pakistani, Korean, Iran, and US adult females, in which high BMI, body fat and visceral fat were risk factors for reporting the prevalence and severity of PMS [55,56,57,58] and menstrual irregularity [59].…”
Section: Discussionsupporting
confidence: 92%
See 3 more Smart Citations
“…However, no significant associations were found between anthropometric factors and PMS prevalence and symptoms. This finding is in line with the findings of Sadler and colleagues in a cross-sectional study on 974 women in the UK [43] and with the recent finding of Isgin-Atici and colleagues who found no significant differences in anthropometric measurements between PMS cases and their counterpart controls in Turkey [31]. However, this contradicts reports in Pakistani, Korean, Iran, and US adult females, in which high BMI, body fat and visceral fat were risk factors for reporting the prevalence and severity of PMS [55,56,57,58] and menstrual irregularity [59].…”
Section: Discussionsupporting
confidence: 92%
“…Reducing consumption of high-fat high calorie/fat/sugar/salt foods may be associated with decreased PMS symptoms by converting estrogen into its inactive form. This was confirmed by recent work from Turkey and Iran, where adolescent girls with PMS reported higher intake of high energy and low nutrient-density foods [31,78]. Further, previous studies reported that female participants with PMS consume fast foods rich in sugar and total fat, caffeinated beverages, snacks, red and fatty meats in higher amounts and more frequently, while rarely consuming dairy products [17,22,79].…”
Section: Discussionsupporting
confidence: 68%
See 2 more Smart Citations
“…This issue of Nutrition & Dietetics includes a collection of original nutrition research that spans these critical first 1000 days of life and beyond. In addition to papers related to pregnancy, 7‐10 infancy 11‐13 and the preschool years, 14 there are papers related to schoolchildren, 15 adolescents 16 and young adults 17,18 …”
mentioning
confidence: 99%